Типологія розвивального освітнього середовища початкої школи - Смолюк, Світлана Володимирівна; Smoliuk, Svitlana V. (Національний університеу біоресурсів і природокористування України, 2016)
У статті на основі вивчення наукової літератури висвітлено типологію освітнього середовища в історико-педагогічному контексті. Виокремлено моделі освітнього середовища: еколого-особистісна, комунікативно-орієнтована, антрополого-психологічна, психодидактична, культурно-освітня, етновиховна, розвивальна. Розкрито взаємозв’язок розвивального освітнього середовища з його складовими: дослідницьким, здоров’язбережувальним, комп’ютерно-орієнтованим, креативним, інноваційним, медійним, естетичним тощо.

In the article on the basis of scientific literature studying the typology of educational environment in historical and pedagogic context was represented. The following models of educational environment were distinguished: ecology-personalized, communication-oriented, anthropological-psychological, psycho-didactic, cultural and educational, ethnology-educational, developing. The article accents the need to strengthen the requirements for the training, developing and education of the modern person; the essence, the basic characteristics and specifics of the developing educational environment and its importance in the formation of a pupil. The developmental educational environment is interpreted as an integrated phenomenon that synthesizes a row of psychological and pedagogic, material and technical, sanitary-hygienic, ergonomic, aesthetical conditions due to cooperation of which pupil’s efficient mastering of socio-cultural experience of mankind is provided, pupil’s personal values are being developed in pedagogic process in elementary school. The author defines the idea that a creating of a developing educational environment is not only a demand of the times, but the pressing need of every person, school, society, since only under such conditions a person has the opportunity to get an education of a good quality, self-realization, assert, act and work creatively. Relationship of the developmental educational environment with its components was disclosed: research, health-protecting, computer-oriented, creative, innovative, medical, aesthetical etc.
Typology of developmental educational environment of elementary school
Keywords: розвивальне освітнє середовище; початкова школа; моделі освітнього середовища; розвиток особистості молодшого школяра; developing educational environment; elementary schools; educational environment models; development of pupil’s personality